Studi Living Tafsir terhadap Tradisi Sekar Sari Kidung Rahayu pada Paguyuban Macapat Tresna Budaya - Wildan Fahdika Ahmad (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2025)
The interpretation of the Qur'an today is no longer just a text of interpretation of the Qur'an collected between two covers. Several studies have shown that the interpretation of the Qur'an lives in society, known as "living interpretation", an extension of the living Qur'an. In this study, the interpretation of Sekar Sari Kidung Rahayu (Sekar Macapat Terjemahanipun Juz 'Amma), by Ahmad Djawahir Anomwidjaja, is the object of research, with the subject of Paguyuban Macapat Tresna Budaya. The purpose of this study is to show how the techniques and philosophy of the practice of living interpretation. The method used to achieve this goal uses a type of qualitative research with interview and observation methods to understand the cultural context and traditional practices. The location of the research is in Bonorowo Village, Bonorowo, Kebumen, and the subjects or informants of the research are traditional practitioners who are members of the Paguyuban Macapat Tresna Budaya group. Data collection techniques were conducted through participant observation, direct observation of the implementation of the tradition, in-depth interviews with key informants, and document analysis of Sekar Sari Kidung Rahayu. The data obtained were analyzed using data triangulation, which combines the results of observation, interviews, and document studies. The results of the study indicate that the interpretation is sung in the macapatan event every Saturday night, one of the goals of which is to understand the Qur'an through macapat songs. Therefore, the interpretation of the Qur'an is no longer just an object to be studied or followed, but is also sung in macapat activities. Macapat as a Javanese artistic tradition becomes a medium that accommodates the 'life' of the interpretation of the Qur'an. Therefore, living interpretation here shows a normative-performative acceptance of interpretation, by a society that has a tradition of discourse on the virtues of the Qur'an and the virtues of macapat.